Representation of Health Messages in Bear Brand’s Advertisement Series Using Barthes’ Semiotics Analysis - Winda Shabrina; Alfrisa Renuat; Dwi Kusuma Ningsih; Yudha Wirawanda (Expose: Jurnal Ilmu Komunikasi, 2022)
In this digital era, advertisement is a form of communication. Messages can be included in advertisements. One example is the Bear Brand advertisement, which broadcasts health messages during the COVID-19 pandemic. Bear Brand is a milk drink brand. As a brand, it has several advertisements in media. The purpose of this study is to analyze health messages in the Bear Brand New Normal series advertisements. This study uses qualitative research methods. This study analyzes advertisements in the official channel of Bear Brand on YouTube. Purposive sampling is used in this study. This study examines the channel's New Normal ad series. This study employs Roland Barthes' semiotic theory to explain the level of signification of the relationship between the signifier and the signified in the Bear Brand advertisement, as well as to describe the denotative and connotative forms and myths in the advertisement. This study also employs Stuart Hall's representation theory to examine the representation of health messages in advertisements that include both verbal and nonverbal cues. The findings of the study show how health messages are represented in advertisements related to the COVID-19 pandemic.